Ульча Кузё: кылбуръёс, поэма : [для среднего школьного возраста] / С. К. Карпов - Карпов Семен Карпович (Удмуртия, 2006)
Экземпляры: (20161201) / Инвентарный номер: 49158 / Цена: 40.00 / Авт.знак: К 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос= Удм)